An analysis of the ’Ludi Saeculares’ of 17 BC: festivity, rituality and power - Silva, Suiany Bueno; Gomes, Erick Messias Costa Otto (Romanitas - Revista de Estudos Grecolatinos, 2016)
Our proposal aims to understand the Secular Games as depicted by the poem Carmen Saeculare of the Roman poet Horace (65-8 BC). The objective is to highlight through its analysis the relevance of the festivity as associated to the mechanisms of power and religiosity. Starting from these premises, we consider that the poem sings a moment of splendor in Rome and highlights the virtues of the Emperor Augustus as the maintainer of the harmony on behalf of the gods and the civic community. Therefore, our discussions start with the analysis of the Carmen Saeculare and the festivity of the Games in 17 BC as representing a ritual moment of thanks to the gods and of celebration of the renewal of the city of Rome by Augustus.